DINAMIKA PEMBELAJARAN TATAP MUKA TERBATAS DI KALANGAN MAHASISWA - Fifit Fitriansyah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
The COVID-19 pandemic has changed the way learning was originally done offline, is now done online. As a result, various uses of learning media are applied to each educator, one of which is learning videos. The purpose of this study was to see the implementation of limited face-to-face learning carried out by students and to see the implementation problems of students' choices in limited face-to-face learning. The research method used is descriptive qualitative analysis. The results of this study show that there are differences in choices where in the first class 80% choose face-to-face learning, while in the second class as much as 71% choose Non-PTM. This shows that the implementation of face-to-face learning is still a polemic among students.